PENGARUH STRUKTUR AKTIVA TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Widayanti, Dwi; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Food and beverage companies are one of the business sectors that continue to experience growth. Food and beverage companies are also in great demand by investors because they are a sector that can survive in the midst of Indonesia's economic conditions. Food and beverage companies have an important role, namely to meet consumer needs. The purpose of this study was to determine the effect of asset structure on firm value with capital structure as an intervening variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. The population of this study were 33 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that the asset structure has a positive but not significant effect on the capital structure, the asset structure has a significant negative effect on firm value, and the capital structure has a positive but not significant effect on firm value. The results of the indirect effect hypothesis test show that the asset structure variable has a positive but not significant effect on firm value through capital structure.